Pengendalian Kebakaran Hutan dan Lahan: Mewujudkan Efektivitas Sebuah Kebijakan - Mutia Rahmah; Muchlis Hamdi (Research and Development Agency Ministry of Home Affairs, 2022)
This research intended to examine and assess how successful the implementation of a public policy regarding the control of land and forest fires is. The approach used in this study is qualitative through inductive description and interpretation. Collecting data using interview techniques, observation, and secondary data. Informants, as primary data sources, were determined through purposive and snowball was carried out with a total of 22 people. The data analysis begins with data collection, simplification and data selection, data presentation, and then drawing conclusions. The technique of determining the validity of the data is using triangulation. The results of this study indicate that the effectiveness of policies related to controlling forest and land fire problems in Bayung Lencir District is still considered not entirely attained, which can be seen from 1) procedural aspects, namely not including the legislature and still lack finance; 2) substantive aspects, namely not yet fully guided by the provisions of higher regulations as a reference, and the level of community participation has not been maximized; 3) the transactive aspect, namely the not yet optimal control of resources; 4) normative aspects, namely the inaccuracy of efforts to prohibit land clearing by burning.